Evaluasi Diagnostik Literasi Digital dan Resiliensi Kognitif Mahasiswa Ilmu Komunikasi - Suyono, Suyono; Lande, Janisa Pascawati; J. Arsyad, Andi Asy'hary; Rosmini, Rosmini (Puslitbang Akademi Relawan TIK Indonesia, 2026)
This study evaluates the digital literacy profile and hoax identification accuracy among first-year communication students using the Indonesian Digital Society Index (IMDI) framework. Adopting an exploratory pilot study approach with a small sample (N=7), the research focuses on providing diagnostic insights for curriculum development in higher education. Data collection involved self-reported competence across ten IMDI indicators and a performance-based test using twelve randomized web contents. Findings reveal a significant disconnect between technical self-defense skills (privacy settings) and critical evaluation abilities (source verification). While students reported high confidence in managing digital privacy, they exhibited a 31% failure rate in detecting hoaxes, particularly those employing authority cues and emotional triggers. The analysis through Elaboration Likelihood Model (ELM) and Truth-Default Theory (TDT) suggests that students frequently rely on peripheral processing routes. This study underscores the urgent need for education interventions that shift focus from administrative digital skills to cognitive resilience.